Estudio de la resistividad a bajas temperaturas de películas delgadas de nitruro de tántalo sintetizadas por pulverización catódica DC - Rodriguez Osorio, Cesar Manuel (2019)
ABSTRACT In this research the resistivity at low temperatures of tantalum nitride thin films were studied, due to the multiple applications that these films have in various industrial fields, and specially in microelectronics and aerospace field; hence the relevance of being able to extend the knowledge about them. The films were synthesized by the direct current sputtering technique, using a silicon substrate (111) and for its characterization, equipment such as X-ray diffractometer, Michelson interferometer, ellipsometer, nanovoltmeter, precision current source and a Fluke digital thermometer. The synthesis process consisted of Ar/ N2 pressure of 5.7 10−3 mb for 10 minutes at a substrate temperature of 470 °C. The DRX analysis indicated the presence of tantalum nitride FCC, network parameter a = 4.35 Å, grain size of 82.6 Å, and a linear relationship in the temperature - dependent resistivity, with resistivity values of 3.4×104Ω. 4.2×104Ω. in the temperature range 296 K – 90 K respectively, considering a film thickness of 60.57 nm. The Temperature Coefficient of Resistance was −1.2×10−9/. From the linear relationship I conclude that the films show a semiconductor behaviour which is reaffirmed with the negative value of the TCR and that the films are ideal for the manufacture of precision electronic components.